Giant cervical teratoma and cerebral arteriovenous malformation: Coincidence or association? - Fink, A. Michelle; Bekhit, Elhamy K. (Journal of Pediatric Neuroradiology, 2013)
Giant congenital cervical teratomas and cerebral arteriovenous malformations (AVMs) are both rare and life threatening. The co-occurrence of these conditions has not previously been described, however new theories regarding the etiology of cerebral AVMs include a “response to injury”. We describe a patient with a vascular giant cystic cervical teratoma diagnosed in fetal life and a cerebral hemorrhage from an ipsilateral AVM later in childhood. We postulate that the development of the AVM may have been related to vascular steal from the tumor in utero. We raise awareness of the potential association of vascular neck masses with intracranial AVMs.
Keywords: Fetal MRI; EXIT procedure; fetal neck mass; cystic teratoma; intracranial AVM